Role of Doppler Ultrasound in the Assessment of Ovarian Torsion and its Correlation with Intraoperative Findings in Gynecological Emergencies - Rizwana Rehman Bazai, Roona Khan, Fahmida Umar, Shazia Saeed, Rehana Kamal, Afshan Mushtaq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ovarian torsion is a gynecologic emergency resulting from the rotation of the ovary on its vascular pedicle, with a resultant compromise of blood flow and subsequent ischemia and necrosis. It is important to diagnose early to prevent irreversible ovarian damage. However, assessment of ovarian vascularity can be made with a non-invasive method, Doppler ultrasound, but its diagnostic reliability should be evaluated. Objective: Thus, the accuracy of Doppler ultrasound in diagnosing ovarian torsion was determined, and preoperative imaging and intraoperative surgical observations were correlated. Methods: A prospective, cross-sectional study was carried out from January 2022 to January 2023 at the Civil Hospital Quetta. Doppler ultrasound was performed in 60 female patients aged 15–45 years with acute lower abdominal pain and clinical suspicion of ovarian torsion, and then surgical exploration was performed. Sensitivity, specificity, and overall accuracy of the Doppler results were compared to intraoperative diagnoses. Results: During surgery, 38 (63.3%) patients were confirmed to have ovarian torsion. In 34 cases, venous flow was absent or reduced, and in 28 cases, there was a reduction of arterial flow. Doppler had sensitivity, specificity, positive predictive value, and negative predictive value of 89.5%, 81.8%, 89.4%, and 81.8%, respectively, while the overall accuracy was 86.7%. Ovarian cysts (52.6%) were the most common associated pathology. Ovarian preservation was higher (68.4%) for patients who presented early. Conclusion: Ovarian torsion is an effective, high-sensitivity, and specific diagnostic modality by Doppler ultrasound. It aids in the timely surgical intervention when used in conjunction with clinical evaluation and improves ovarian salvage outcomes. Keywords: Ovarian torsion, Doppler ultrasound, gynecological emergency, adnexal mass, ovarian salvage, diagnostic accuracy.